Does model type influence the effectiveness of combined action observation and motor imagery training for novices learning an Ankle Pick takedown? - Chye, Samantha; Chembila Valappil, Ashika; Knight, Ryan; Greene, Andrew; Shearer, David; Frank, Cornelia; Diss, Ceri; Bruton, Adam (Frontiers in Psychology, 2025)
IntroductionCombined action observation and motor imagery (AOMI) training has been shown to facilitate motor skill performance, but limited research has explored its effectiveness on motor learning and factors that may moderate the effects of the intervention. This study examined the influence of model type on the effectiveness of AOMI training for novices learning an Ankle Pick takedown.MethodsTwenty-eight novice participants (M = 28.07 ± 7.29 years) were randomly assigned to a control condition (n = 8), or to AOMI training that displayed footage of a self-model (AOMISELF; n = 10) or other-model (AOMIOTHER; n = 10). All training conditions included physical practice. A motor learning design incorporating pre-test (Day 1), acquisition (Days 2–6), post-test (Day 7), and retention-test (Day 14) was utilized. Motor skill performance, self-efficacy and mental representation structures were recorded as measures of learning.ResultsThere were no significant differences between the training conditions across all twelve kinematics measures of motor skill performance. Self-efficacy scores increased for all training conditions over time. Both the AOMIOTHER and Control conditions led to improved functional changes in mental representation structures while the structures for the AOMISELF condition became less similar to the reference structure over time.DiscussionCollectively, the largely null findings (n = 13, 92.86%) suggest that physical practice has the strongest influence on motor adaptations for this complex motor skill at these early stages of learning. However, the findings also suggest model type may be an important factor for novices using AOMI training. It is recommended that future research explores alternative modeling approaches, such as mixed-modeling incorporating both self- and other- footage, when designing AOMI interventions for sport.